РЕДОКС-ЗАЛЕЖНІ ОСОБЛИВОСТІ ЖИРОВОЇ ТКАНИНИ, ПУХЛИНИ, НЕЙТРОФІЛІВ ТА ТРОМБОЦИТІВ У ХВОРИХ НА МЕТАСТАТИЧНИЙ КОЛОРЕКТАЛЬНИЙ РАК - Burlaka, A.P.; Virko, S.V.; Burlaka, A.A.; Krupnyk, K.L. (PH Akademperiodyka, 2023)
Summary. Aim: To study the levels of redox-forming molecules generated in tumor, adipose tissue (AT), neutrophils and platelets of patients with colorectal cancer (CRC) with normal body weight or obesity. Materials and Methods: 83 samples of tumor tissue and 83 samples of the AT taken at the distance of 5 cm from the tumor as well as 83 blood samples have been analyzed in the patients with CRC with metachronous lesions in liver. The comparison group consisted of 18 patients who were surgically treated for ulcer. The rates of free radical generation were measured by electron paramagnetic resonance. Results: Free radical generation rate in tumor tissue and AT increased and nitrogen oxide (NO) levels decreased in patients with body mass index ≥ 25 kg/m2 as compared to the patients with normal body weight (p < 0.05). The superoxide generation activity in neutrophils of CRC patients exceeded about 7-fold the values obtained in neutrophils from patients with ulcer while the NO levels produced by neutrophils of CRC patients decreased significantly (p < 0.01). The same trends held true for the platelets. Conclusions: In obese patients with CRC, superoxide-generating activity increases in cancer cells, AT, neutrophils and platelets. The obesity should be considered as the additional oncological risk representing the potent predictor for the events realized in obese patients such as oxidative stress, inflammation, insulin resistance and endothelial dysfunction.